Networking and the prevention of drug use with adolescents: an integrative review (Research, Society and Development, 2022)
Networking has proven to be effective in preventing the use and abuse of alcohol and other drugs with children and adolescents, however, there are many challenges in the effectiveness of this action, Therefore, this review aims to analyze the networking developed with adolescents for the prevention of drug use in the scientific production of articles in the Brazilian context. To this end, an investigation was conducted on publications from January 1, 2006 to December 31, 2020, in the BVS and Periódico Capes databases. After evaluating the inclusion/exclusion criteria, 6 articles were retrieved and analyzed. The findings were organized into two thematic axes that dealt with intersectorial work and networking with adolescents. It is noteworthy that a group of articles dealt more specifically with "Understanding of actors about drugs and their impacts on networking", and another group, about "Diagnosis and evaluation of programs focused on networking". In a broad way, it was possible to apprehend that the importance of networking was perceived by the research participants, but several difficulties were presented for the accomplishment of this work. It was also observed the scarcity of actions related to the prevention of drug use and abuse and to health promotion, confirming the need for further development of practical actions in the area.